2021
DOI: 10.1002/er.6773
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting polysulfides with PDA / PEI‐functionalized separators for stable lithium‐sulfur batteries

Abstract: Summary Lithium‐sulfur batteries are considered the most promising candidates for energy storage materials in the future, but the shuttle of polysulfides has seriously affected the development of lithium‐sulfur batteries. Because the surface morphology of the material determines its structural properties to some extent. Therefore, the surface of celgard‐2400 is structurally modified by controlling the polymerization of dopamine to further improve the performance of the separator. Utilizing the effective adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…While greater PAA grafting improved LiPS rejection via highly selective ionic sieving, the composite membrane exhibited greater hydrophobicity, which decreased electrolyte wettability and, consequently, ionic conductivity. In more recent work, Pei et al 144 similarly found that appending a polydopamine (PDA) layer to a Celgard membrane reduced average pore sizes by 35% (130 nm). However, the PP/PA membrane surface was rough with only PDA.…”
Section: Polymer-based Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While greater PAA grafting improved LiPS rejection via highly selective ionic sieving, the composite membrane exhibited greater hydrophobicity, which decreased electrolyte wettability and, consequently, ionic conductivity. In more recent work, Pei et al 144 similarly found that appending a polydopamine (PDA) layer to a Celgard membrane reduced average pore sizes by 35% (130 nm). However, the PP/PA membrane surface was rough with only PDA.…”
Section: Polymer-based Modificationsmentioning
confidence: 99%
“…142 Hydrophilic functional groups in common polymers also improve electrolyte wettability for improved Li-ion conduction. 144 Despite all the benefits of using polymer modifiers, common polymer modifications alone are usually insufficient in mitigating the shuttle effect and do not significantly improve the rate capability of LSBs, limiting their charge rate and power density.…”
Section: Polymer-based Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] Of these, separator modification and functionalization provide an attractive solution by virtue of its simplicity and effectiveness. [13][14][15] As an important part of Li-S batteries, the separator prohibits the cutting-out of batteries and acts as the channel to transport lithium ions between electrodes. Currently, polyolefin microporous membranes prepared by melt-stretching method are commonly used for Li-S batteries as it owns advantages of high chemical stability and low interfacial impedance.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at these issues, numerous efforts have been devoted to this area 6‐12 . Of these, separator modification and functionalization provide an attractive solution by virtue of its simplicity and effectiveness 13‐15 …”
Section: Introductionmentioning
confidence: 99%